Lima Skill Wajib Mahasiswa: Relevan terhadap Karier Masa Depan? - Aulia Adisty Ramdhani; Masduki Asbari; Charlina Nur Assyifa (Journal of Information Systems and Management (JISMA), 2023)
The main purpose of this research is to determine the influence of the skills that college students must have on improving their career in the future. This research used descriptive qualitative method as its method by using a secondary data from one of Sherly Annavita Rahmi's YouTube channel video entitled "These are the 5 Mandatory Skills for College Students”. The results of this research are students are given an overview of 5 (five) skills, such as having the courage to explore their own potential, being consistent and persistent, being willing and able to adapt, prioritizing a good attitude, and having empathy that maximized during the college with the hope that they will not only have good academic abilities but also have soft skills that useful for their social life, especially in the work life.